Stress Cracking Behavior of Interstitial Matrix and Cement Line Interface Deflection - Nor Syazwani Izzati Raja Ali, Raja; Daud, Ruslizam; Khairul Ali Hassan, Muhammad; Alia Md Zain, Noor; Najwa Mansor, Nurul (International Journal of Engineering and Technology, 2018)
Bone can be noticed as a complex hierarchically organized structures at several length scales, which has both metabolic and mechanical functions. One of the major type of bone is known as cortical bone as it comprises of distinct microstructures including osteons, interstitial bone, and cement line which play an important role in examining the fracture behavior in cortical bone. Microcracking of these unique features may lead to bone fracture. To date, there are a few of studies have been done regarding to its special microstructures. However, the mechanical properties of cement line is absently described to predict the cracking behavior at micro-scale level. This study aims to determine the stress distribution of cement line deflection in single osteon using finite element (FE) method. A FE analysis were performed to simulate the secondary osteon model under mode I, mode II and mixed-mode loading. The finding of this study propose the stress is accumulated near to the cement line. The maximum stress may be found to be high at the longest crack. The study concluded that the stress cracking behavior of cement line deflection is influenced by different mode of loading.Â Â